Prevensi Gerakan Tanah Jenis Longsor Lereng di Dusun Riang Negeri Tawiri Kecamatan Teluk Ambon, Kota Ambon - Matheus Souisa; Pieldrie Nanlohy; Sisca M. Sapulete; Alexander Y. Elake; Mirella F. Maahury (Jurnal Gema Ngabdi, 2023)
Disaster prevention is carried out to prevent and minimize the occurrence of natural disasters such as landslides. Prevention is at the heart of natural disasters and must be supported by community knowledge about disaster management in the form of pre-disaster, during-disaster, and post-disaster views from a scientific and technical perspective. Inadequate knowledge will have an impact on less-than-optimal responses in disaster prevention and mitigation. One of the efforts to increase the community's role in preventing natural disasters is through Community Service (PKM) activities using the geo-forestry method by planting shade trees at the location of former landslides and the potential for landslides in RT.02/RW.07 Riang, Tawiri Village, Teluk Ambon District. This activity is carried out through the transfer of knowledge about, Land Movement Physics, Environmental Geophysics, and Disaster Mitigation. Service activities are expected to reach the Disaster Volunteer Team in Riang, Tawiri Village, namely by increasing the network of cooperation with Disaster Volunteers and establishing synergies with Geoscience Volunteers and the Unpatti Faculty of Mathematics and Natural Sciences.